The Role of Equity Funds in the Financial Crisis Propagation - CHUA, Choong Tze (Institutional Knowledge at Singapore Management University, 2011)
The early stage of the recent financial crisis was marked by large value losses for bank stocks. This paper identifies the equity funds most affected by this valuation shock and examines its consequences for the non-financial stocks owned by the same funds. We find that (i) ownership links to “distressed equity funds” relate to large underperformance for the most exposed stocks and contribute an additional 10% to the overall stock market downturn; (ii) distressed fire sales and the associated price discounts are concentrated among the best performing stocks; and (iii) stock with a high share of fund ownership generally performed much better throughout the crisis.